Cell Line Derived from a Murine Sarcoma Virus (Moloney Pseudotype)-Induced Tumor: Cultural, Antigenic, and Virological Properties - Massicot, J. G. (1971)
A cell line derived from a murine sarcoma virus (Moloney pseudotype)-induced tumor has been established. It retains oncogenicity, releases both sarcoma and leukemia viruses, and has virus-induced cellular antigens.